CONTRIBUTION OF IVANO-FRANKIVS’K INSTITUTE OF OIL AND GAS (IFING) TO THE PERSONNEL TRAINING FOR OF OIL AND GAS COMPLEX OF UKRAINE (1967-1994) - Мандрик, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the history of creation and activity of Ivano-Frankivs’k institute of oil and gas, personnel training in it’s considered for oil and gas complex of Ukraine.